Transport properties of topologically non-trivial bismuth tellurobromides BinTeBr - Pabst, Falk; Hobbis, Dean; Alzahrani, Noha; Wang, Hsin; Rusinov, I. P.; Chulkov, E.; Martina, Joshua; Ruck, Michael; Nolas, George S. (Journal of Applied Physics, 2019)
Temperature-dependent transport properties of the recently discovered layered bismuth-rich tellurobromides BinTeBr (n = 2, 3) are investigated for the first time. Dense homogeneous polycrystalline specimens prepared for different electrical and thermal measurements were synthesized by a ball milling-based process. While the calculated electronic structure classifies Bi2TeBr as a semimetal with a small electron pocket, its transport properties demonstrate a semiconductorlike behavior. Additional bismuth bilayers in the Bi3TeBr crystal structure strengthens the interlayer chemical bonding thus leading to metallic conduction. The thermal conductivity of the semiconducting compositions is low, and the electrical properties are sensitive to doping with a factor of four reduction in resistivity observed at room temperature for only 3% Pb doping. Investigation of the thermoelectric properties suggests that optimization for thermoelectrics may depend on particular elemental substitution. The results presented are intended to expand on the research into tellurohalides in order to further advance the fundamental investigation of these materials, as well as investigate their potential for thermoelectric applications.
CRIS-Team Scopus Importer:2022-04-14